(untitled) (The Harvest, 2024)
It is clear that the total size of the economy and the total volume of trade have been increasing in Nepal. Both export trade and import trade contribute to economic growth, but the trade deficit increased rapidly over two decades. This paper investigates the trend analysis of foreign trade and GDP growth of Nepal during the last two decades. This paper has used annual statistical data from fiscal year 2001/02 to 2022/ 23 to analyze the trend of GDP growth and foreign trade of Nepal. Obviously, export and import trade play a crucial role in the economic growth of Nepal, but considering the fact of serious trade deficit, policy implications should be concentrated on exportoriented economic growth rather than import-oriented economic growth.